The survival rate of neonates in Pakistan: Problems in health care access, quality and recommendations - Muhammad Muzzamil; Maryam Nisa; Shaeroz Raza (Tabriz University of Medical Sciences, 2022)
There is a high prevalence of infant mortality in South Asia and other parts of Asia, but overall, the bulk of neonatal deaths occur in developing countries. Although Pakistan has made great strides in the past decade to reduce child mortality with the help of foreign donors and the government, very little progress has been made in reducing neonate and infant mortality. Several studies have demonstrated the potential for low-cost therapies to greatly reduce neonatal mortality by helping pregnant mothers and their newborns. We need to shed light on the efforts and problems surrounding this topic in order to find and implement solutions backed by research to lower newborn mortality. This brief overview was produced using international standards for conducting reviews. Researchers opted for an explanatory methodology. Our findings were based on research conducted through PubMed, Google's literature database, Journals Online, and the Internet Library. All of the works consulted primary sources, such as the World Health Organization (WHO) and the World Bank. The desired findings were obtained by using the term "neonatal mortality." The study's authors were interested in tracking variations in neonatal mortality over time. The increasing prevalence of neonatal death in Pakistan emphasizes the need for policies and programs that prioritized the health of children. Neonatal survival can be improved with the help of basic obstetric and newborn care in Pakistan.